Precarious employment and migrant workers' mental health: a systematic review of quantitative and qualitative studies - Ozlem Koseoglu Ornek; Julia Waibel; Pia Wullinger; Tobias Weinmann (Nordic Association of Occupational Safety and Health (NOROSH), 2022)
OBJECTIVES: Evidence suggests that precarious employment can have detrimental effects on workers' health, including mental health. Migrant workers are discussed to be especially vulnerable to such effects. Thus, we systematically reviewed existing research on the association between precarious employment and migrant workers' mental health. METHODS: Three electronic databases (Web of Science, PsycINFO and PubMed/Medline) were searched for original articles on quantitative and qualitative studies published from January 1970 to February 2022 in English, German, Turkish and Spanish. Multiple dimensions of precarious employment were considered as exposure, with mental health problems as outcomes. Narrative synthesis and thematic analyses were performed to summarize the findings of the included studies along with risk of bias and quality assessment. RESULTS: The literature search resulted in 1557 original articles, 66 of which met the inclusion criteria - 43 were of high quality and 22 were of moderate quality. The most common exposure dimensions analyzed in the studies included temporariness, vulnerability, poor interpersonal relationships, disempowerment, lacking workers' rights and low income. The outcome measures included stress, depression, anxiety and poor general mental health. The prevalence of these outcomes varied between 10-75% among the included quantitative studies. All qualitative studies reported one or more dimensions of precarious employment as an underlying factor of the development of mental health problems among migrants. Of 33 quantitative studies, 23 reported evidence for an association between dimensions of precarious employment and mental health. CONCLUSION: The results of this review support the hypothesis that precarious employment is associated with migrant workers' mental health.